Option Valuation : a First Course in Financial Mathematics. - Junghenn, Hugo D. (Chapman & Hall/CRC financial mathematics series., 2011)
Interest and Present ValueCompound Interest Annuities Bonds Rate of ReturnProbability SpacesSample Spaces and Events Discrete Probability Spaces General Probability Spaces Conditional Probability IndependenceRandom VariablesDefinition and General Properties Discrete Random Variables Continuous Random Variables Joint Distributions Independent Random Variables Sums of Independent Random VariablesOptions and ArbitrageArbitrage Classification of Derivatives Forwards Currency Forwards FuturesOptions Properties of Options Dividend-Paying StocksDiscrete-Time Portfolio ProcessesDiscrete-Time Stochasti.